Strength-Based Counseling (SBC): A Key Approach to Strengthening Adolescent Resilience in the Face of Social Media Challenges - Susanti, Desy; Agustine, Tiara (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Social media has become an integral part of adolescents' lives, but it also brings negative impacts such as social pressure, depression, and anxiety. This study aims to evaluate the effectiveness of Strength-Based Counseling (SBC) in increasing adolescent resilience to social media pressure through the Systematic Literature Review (SLR) method. The data used came from 321 articles which were then filtered into 10 articles that met the inclusion criteria. this study identified that SBC is effective in helping adolescents manage emotional stress, reduce the negative impacts of social media, and improve mental health and psychological resilience. Strength-Based Counseling focuses on developing individual strengths, such as self-control, positive thinking skills, and emotional management, which have been shown to significantly increase resilience. These results indicate the potential of SBC as a relevant and applicable counseling approach in educational settings to support adolescent well-being in the digital era.